Penggunaan ZnO/Zeolit dalam Degradasi Fenol Secara Fotolisis dan Aplikasinya Pada Limbah Karet - Zilfa, Z.; Wilda Putri Suhada; Rahmiana Zein (Jurnal Kimia Unand, 2023)
Phenol is one of the organic compounds that are toxic and carcinogenic. In this study ZnO/zeolite was used to degrade phenol by photolysis and its application to rubber waste. Phenol analysis was performed using a UV-Vis spectrophotometer and Fourier Transform Infrared (FTIR), while the ZnO/zeolite characterization used FTIR and X-Ray Diffraction (XRD). The results showed that the percentage of phenol degradation without a catalyst was 15.79% with UV irradiation for 75 minutes and increased to 79.63% with the addition of 0.4 g ZnO/zeolite. Phenol degradation in rubber wastewater samples using ZnO/zeolite obtained a degradation percentage of 58.28%. Phenol analysis before and after degradation showed a shift in wave number which indicated the occurrence of degradation. Characterization of ZnO/zeolite before and after degradation using FTIR and XRD showed that there was no change in the structure of ZnO/zeolite